A study of Thalaiyial in Sivapuranam and the understanding among Malaysian religious teachers - Vasudevan Letchumanan (Tanjong Malim, 2021)
A study of Thalaiyial in Sivapuranam and the understanding among Malaysian religious teachers by Vasudevan Letchumanan